Tetracycline-inducible shRNA targeting antisense long non-coding RNA HIF1A-AS2 represses the malignant phenotypes of bladder cancer. Issue 1 (28th June 2016) - Chen, Mingwei; Zhuang, Chengle; Liu, Yuchen; Li, Jianfa; Dai, Fen; Xia, Ming; Zhan, Yonghao; Lin, Junhao; Chen, Zhicong; He, Anbang; Xu, Wen; Zhao, Guoping; et al.
Highlights: HIF1A-AS2 was up-regulated as oncogene in bladder cancer. "Tet-on" shRNA switch quantitatively silenced HIF1A-AS2 and suppressed bladder cancer progression as an amplifier by dosage-dependent manner. It is a therapeutic method for bladder cancer. Abstract: Various studies have indicated that long non-coding RNAs (lncRNAs) play vital roles in the cancer development and progression. LncRNA hypoxia inducible factor 1alpha antisense RNA-2 (HIF1A-AS2) is upregulated in gastric carcinomas and knockdown of HIF1A-AS2 expression by siRNA could inhibit cell proliferation in vitro and tumorigenesis in vivo. Inspired by these observations, we hypothesized that HIF1A-AS2 possibly plays the analogous roles in bladder cancer. In our study, we first reported that HIF1A-AS2 was up-regulated in bladder cancer tissues and cells, and HIF1A-AS2 expression level in bladder cancer tissues is positively associated with advanced clinical pathologic grade and TNM phase. Cell proliferation inhibition, cell migration suppression and apoptosis induction were observed by silencing HIF1A-AS2 in bladder cancer T24 and 5637 cells. Overexpression of HIF1A-AS2 in SV-HUC-1 cells could promote cell proliferation, cell migration and anti-apoptosis. Besides, we utilized the emerging technology of medical synthetic biology to design tetracycline-inducible small hairpin RNA (shRNA) vector which specifically silenced HIF1A-AS2 in a dosage-dependent manner to inhibit the progression of human bladder cancer. In conclusion, our data suggested that HIF1A-AS2 plays oncogenic roles and can be used as a therapeutic target for treating human bladder cancer. Synthetic "tetracycline-on" switch system that quantitatively controlled the expression of HIF1A-AS2 in bladder cancer can inhibit the progression of bladder cancer cells in a dosage-dependent manner. Our findings provide new insights into the role of the lncRNA HIF1A-AS2 in the bladder cancer.